The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.3233/jad-160504
|View full text |Cite
|
Sign up to set email alerts
|

Five-Year Longitudinal Brain Volume Change in Healthy Elders at Genetic Risk for Alzheimer’s Disease

Abstract: Neuropathological changes associated with Alzheimer’s disease (AD) precede symptom onset by more than a decade. Possession of an Apolipoprotein-E (APOE) ε4 allele is the strongest genetic risk factor for late onset AD. Cross-sectional studies of cognitively intact elders have noted smaller hippocampal/medial temporal volumes in ε4 carriers (ε4+) compared to ε4 non-carriers (ε4-). Few studies, however, have examined long-term, longitudinal, anatomical brain changes comparing healthy ε4+ and ε4- individuals. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
39
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 56 publications
4
39
0
Order By: Relevance
“…Higher baseline NfL levels were associated with greater volumetric decline in left hippocampus (33.2 mm 3 /y, p < 0.001) and mid anterior corpus callosum (7.68 mm 3 , p = 0.015), with a trend seen in the left amygdala, right thalamus, and mid corpus callosum. Higher baseline tau levels were not correlated with regional volumetric changes.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Higher baseline NfL levels were associated with greater volumetric decline in left hippocampus (33.2 mm 3 /y, p < 0.001) and mid anterior corpus callosum (7.68 mm 3 , p = 0.015), with a trend seen in the left amygdala, right thalamus, and mid corpus callosum. Higher baseline tau levels were not correlated with regional volumetric changes.…”
Section: Resultsmentioning
confidence: 92%
“…Previous work has suggested that monitoring regional brain volumes through MRI may serve as a potential tool to recognize and follow structural brain changes. 3 Measurement of hippocampal volumes has been well-studied in Alzheimer disease (AD) and is commonly used as a secondary outcome measure in AD clinical trials. 4 Similarly, we and others have reported associations between volumes of certain brain regions and exposure to RHI as well as clinical outcomes in cross-sectional studies.…”
mentioning
confidence: 99%
“…Longitudinal studies are crucial to identify genetic and environmental factors that influence the rate of these brain changes throughout development (Giedd et al, 1999;Gogtay et al, 2004;Shaw, Gogtay, & Rapoport, 2010) and aging (Raz et al, 2005). Interindividual differences in brain development are associated with general cognitive function (Ramsden et al, 2011;Schnack et al, 2015;Oschwald et al, 2019), and risk for psychiatric disorders (Shaw et al, 2009;Liberg et al, 2016) and neurological diseases (Reiter et al, 2017;Eshaghi et al, 2018;Jiskoot et al, 2019). Genetic factors involved in brain development and aging overlap with those for cognition (Brans et al, 2010;Brouwer et al, 2014) and risk for neuropsychiatric disorders (Brans et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…However, the number of studies investigating effects of APOE polymorphisms on hippocampal subfields in healthy cohorts is very limited and the results have been inconsistent so far (de Flores et al, 2015). While some studies found that APOE ϵ2 carriers had smaller volumes in CA3/DG subfield (Mueller, Schuff, Raptentsetsang, Elman, & Weiner, 2008;Mueller & Weiner, 2009), others suggested these effects were limited to the Sub (Burggren et al, 2008;Donix et al, 2010) or affected all three subfields (Reiter et al, 2017). In addition, the associations between BDNF polymorphisms and hippocampal subfields and hippocampal subregions have not yet been investigated in healthy populations.…”
Section: Introductionmentioning
confidence: 99%